Exploration of Students Challenges and Solutions: A Qualitative Description of The Learning Process In Creating Tree Diagrams for Prospective English Language Teachers - Pratiwi, Putri Adinda; Mashalani, Fahima; Hafizhah, Maulia; Harahap, Nur Hapsi; Ismahani, Siti (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The use of tree diagrams serves as a valuable tool for students to grasp the structure of a sentence and conduct analyses based on both its surface and deep structures. Proficiency in creating syntactic tree diagrams can be employed as an indicator of a student's ability to scrutinize sentences and their structures comprehensively. While conducting this research, We found a lot of articles about tree diagrams in syntax. However, we haven't seen many articles that discuss students' challenges and solutions when learning tree diagrams, particularly for teachers. This research used descriptive and qualitative methods. We conducted interviews, both directly or through messages, with a few participants from the same department at a University. In this research, researchers took 6 student participants. Categorization challenges emerge as a central concern, with participants highlighting the difficulty in identifying and categorizing words within a sentence. This underscores the necessity for learners to develop a robust grasp of parts of speech and their respective functions in constructing meaningful tree diagrams